Radiographic Evaluation of Chronic Static Scapholunate Dissociation Post Soft Tissue Reconstruction - Yang, Yong; Kumar, Kannan K.; Tsai, Tsu-Min (Journal of Wrist Surgery, 2013)
The purpose of this study was to examine the radiographic outcomes of dorsal intercarpal ligament capsulodesis (DILC), documenting the time to carpal collapse postoperatively. From January 2008 to January 2011, 12 patients were identified with chronic scapholunate (SL) dissociation. The average follow-up period was 15.8 months. Paired t-tests were used preoperatively, one month after pin removal, and at final follow-up to determine significance in radiographic outcomes. The Disabilities of the Arm, Shoulder, and Hand (DASH) survey was administered to patients before and after surgery to assess subjective levels of pain, function, and satisfaction. Intraoperatively all deformities were reduced completely. One month after pin removal, the mean SL gap was 3.3 mm, the SL angle was 74°, the radiolunate (RL) angle was 17°, and the lunatocapitate (LC) angle was 8°. Only the SL angle improved; the other measurements remained unchanged. At final follow-up, the mean SL gap was 3.6 mm, the SL angle was 78°, the RL angle was 20°, and the LC angle was 10°. SL angle worsened, but with no statistically significant difference. The other radiographic measurements remained unchanged at final follow up. Wrist flexion and extension decreased from 76% and 69% of the contralateral side to 62% and 56% of the contralateral side after surgery. Grip strength was 64% of the contralateral side before surgery and 83% after surgery. Visual Analog Scale (VAS) results improved from 6.3 to 1.7, and DASH scores improved from 39 to 8 after the surgery. DILC cannot withstand large and repetitive forces. Carpal collapse recurred within a short time after DILC. However, our small patient numbers and short term follow-up preclude any conclusions with respect to clinical efficacy of this procedure. Limitations of this study include the fact that this is a retrospective study with no control group. In addition, it represents a single-surgeon series, which introduces a source of bias and carries the risk of technical and methodological flaws, which may have contributed to the observed radiographic outcomes.
Keywords: chronic scapholunate dissociation; reconstruction of scapholunate ligament; radiographic evaluation scapholunate reconstruction